Uber App Users’ Satisfaction and Intention to Continue Using It: Expanding the Expectation Confirmation Model - Rana, Md. Sohel; Aubhi, Rezwan Ul Haque; Sharmin, Shadia; Amin, Mohammad Bin; Földi, Kata; Degago, Esayas; Mollah, Md. Alamgir; Molnar, Edina (Journal of Posthumanism, 2025)
This study expands the Expectation Confirmation Model (ECM), with the purposes to investigate the influencing factors of user satisfaction and continuance intention with respect to the Uber ride sharing application. Although ECM in the context of Information Systems (IS) has been applied broadly, its use has been limited in mobile service platforms, particularly in Uber. The study focuses on the relationships between user satisfaction, perceived usefulness, confirmation of expectations, perceived trust and user experience quality using a quantitative approach. Hypothesis testing results show that all proposed constructs significantly affect continuance intention and perceived trust proved to be the strongest predictor. More specifically, including trust into the integration of user experience quality, these complexities liberate the ECM from a cognitive approach by incorporating emotional and experiential evaluation of trust. These findings support the IS continuance behavior literature and extend theoretical frameworks with insights based on the Technology Acceptance Model and user experience research. Besides validating ECM in a new domain, this work also provides practical implications to digital service providers who want to keep users more permanent in mobile app ecosystems.